Siemens Reloaded: Chloride‐Assisted Selective Hydrodechlorination of SiCl4 to HSiCl3. Issue 5 (26th January 2023) - Sturm, Alexander G.; Karaca, Uhut S.; Heinz, Myron; Felder, Thorsten; Lewis, Kenrick M.; Auner, Norbert; Holthausen, Max C.
Abstract: Trichlorosilane is the key intermediate for the large‐scale production of polycrystalline silicon in the Siemens and Union Carbide processes. Both processes, however, are highly inefficient, and over two thirds of the trichlorosilane employed is converted to unwanted silicon tetrachloride accumulating in millions of tons per year on a global scale. In this combined experimental and theoretical study we report an energetically and environmentally benign synthetic protocol for the highly selective conversion of SiCl4 to HSiCl3 using organohydridosilanes as recyclable hydrogen transfer reagents in combination with onium chlorides as efficient catalysts. We put the same protocol to further use demonstrating the quantitative conversion of higher oligosilane residues, which form as another unwanted and potentially hazardous byproduct of Siemens processes, to HSiCl3 in a low‐temperature recycling step. Abstract : Millions of tons of SiCl4 are being incinerated every year – simply due to a lack of alternatives. What if we could reintroduce this unwelcome by‐product of the polysilicon production back into the supply chain? We present a selective and quantitative protocol to re‐convert SiCl4 to HSiCl3 under ambient conditions.